Unified enantioselective total synthesis of 3, 6-dioxygenated diketopiperazine natural products, diatretol and lepistamides A, B and C. (16th March 2021) - Takahashi, Shu; Kimishima, Aoi; Hirose, Tomoyasu; Yamada, Takeshi; Sugawara, Akihiro; Shirahata, Tatsuya; Noguchi, Yoshihiko; Iwatsuki, Masato; Hokari, Rei; Ishiyama, Aki; Kobayashi, Yoshinori; Sunazuka, Toshiaki
Graphical abstract: Highlights: Total synthesis and determination of the absolute configuration of Dietretol was accomplished. This synthetic approach involves the use of a folded conformation, caused by the distinctive intramolecular CH/π interaction. The total synthesis of Lepistamides were realized by utilizing of the synthetic approach of Dietretol. Abstract: The concise enantioselective total synthesis of Diatretol (1) has been achieved via 9 steps with 30％ yield. The synthetic approach involves stereoselective oxidation and regioselective transacetalization utilizing a folded conformation induced by an intramolecular CH/π interaction. In addition, we have also achieved total synthesis of three diketopiperazine natural products, Lepistamides A (2), B (3) and C (4).